The effect of acetylcysteine on the prothrombin time and international normalized ratio: a narrative review - Nazar, Messia; Kootstra-Ros, Jenny E.; Mian, Paola; Touw, Daniel J.; Sturkenboom, Marieke G. G. (Clinical toxicology (Philadelphia, Pa.), 2025)
Patients poisoned with paracetamol are treated with acetylcysteine. In patients without hepatocellular injury, an increased prothrombin time or international normalized ratio has been observed during acetylcysteine administration. The international normalized ratio is preferred as it is a standardized calculation of prothrombin time independent of reagents and machinery. Since the prothrombin time and international normalized ratio are used as markers of liver injury in patients with paracetamol poisoning, it is important to assess the magnitude of the effect of acetylcysteine treatment on the prothrombin time and international normalized ratio. The aim of this narrative review is to describe the effect of acetylcysteine on the prothrombin time and international normalized ratio. Embase, PubMed and Web of Science were searched to identify the effect of acetylcysteine on coagulation factors II, VII, IX or X, the prothrombin time and the international normalized ratio in and studies in healthy subjects and clinical studies involving both those poisoned with paracetamol and surgical patients. The search terms employed were acetylcysteine combined with prothrombin time, international normalized ratio, coagulation or haemostasis. The search identified a total of 2,471 articles, of which 19 studies were included. Six and/or studies, five clinical studies in paracetamol-poisoned patients and eight clinical studies in surgical patients were included. Acetylcysteine caused a 15-30% increase in prothrombin time and international normalized ratio. This increase was dose-dependent and was caused by a decrease in the activity of coagulation factors II, VII, IX and X. The effect of acetylcysteine on the increased prothrombin time and international normalized ratio was more prominent after the high loading dose but remained present during the lower maintenance dose of acetylcysteine. The effect was observed in both and studies and confirmed in clinical studies in paracetamol-poisoned patients without hepatic injury. Studies in surgical patients treated with acetylcysteine showed conflicting results. Twelve of the 13 clinical studies suffered from risk of bias, limiting the value of these studies. The moderate 15-30% increase in the international normalized ratio induced by acetylcysteine is especially important in hospitals using the international normalized ratio as a marker for hepatotoxicity due to paracetamol poisoning and underlines the need for the international normalized ratio to be assessed at admission. Acetylcysteine treatment leads to an estimated 15-30% increase in prothrombin time and international normalized ratio in both experimental studies and paracetamol-poisoned patients. Isolated increases in prothrombin time and international normalized ratio during acetylcysteine infusion are common and do not necessarily reflect liver dysfunction or liver injury.